2005
DOI: 10.1037/0021-9010.90.6.1054
|View full text |Cite
|
Sign up to set email alerts
|

An Episodic Process Model of Affective Influences on Performance.

Abstract: In this article, the authors present a model linking immediate affective experiences to within-person performance. First, the authors define a time structure for performance (the performance episode) that is commensurate with the dynamic nature of affect. Next, the authors examine the core cognitive and regulatory processes that determine performance for 1 person during any particular episode. Third, the authors describe how various emotions and moods influence the intermediary performance processes, thereby a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
1,131
1
20

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 851 publications
(1,188 citation statements)
references
References 113 publications
(140 reference statements)
36
1,131
1
20
Order By: Relevance
“…In addition, recent studies have also started to investigate momentary episodes of work engagement (Sonnentag, 2003) and performance (Beal, Weiss, Barros, & MacDermid, 2005), and concluded that meaningful variations exist not only at the between-person, but also at the within-person level. Therefore, the purpose of the present study is to test, for the first time, how variations in job resources may determine state levels of work engagement, through the enhancement of employees' state self-efficacy beliefs over time.…”
Section: The Present Studymentioning
confidence: 99%
“…In addition, recent studies have also started to investigate momentary episodes of work engagement (Sonnentag, 2003) and performance (Beal, Weiss, Barros, & MacDermid, 2005), and concluded that meaningful variations exist not only at the between-person, but also at the within-person level. Therefore, the purpose of the present study is to test, for the first time, how variations in job resources may determine state levels of work engagement, through the enhancement of employees' state self-efficacy beliefs over time.…”
Section: The Present Studymentioning
confidence: 99%
“…Such studies could examine recovery processes at the day level and could therefore shed more light onto shorter-term processes related to the maintenance of positive mood and performance capability. For example, the recovery experience scales can be applied when extending research on episodic models of performance (Beal, Weiss, Barros, & MacDermid, 2005). It would be particularly interesting to examine if recovery experiences can explain day-level variations in performance.…”
Section: Suggestions For Future Research and Potential Applicationsmentioning
confidence: 99%
“…To the extent that an individual is burdened with too many distracting stimuli that tap these resources, performance on other tasks will suffer (Schneider & Fisk, 1982). Given that affective states redirect attentional focus from the task to the affective experience particularly strong (Beal, Weiss, Barros, & MacDermid, 2005), exposure to parents' arguments may undermine children's short-term attention by disrupting their ability to focus and sustain attention. The purpose of the current study is to examine this assumption taking into consideration children's physiological reactivity to simulated conflict and their parental conflict history as moderators in an experimental approach, using an analogue design.…”
mentioning
confidence: 99%